1991
DOI: 10.1111/j.1360-0443.1991.tb01704.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of depressive symptomatology and alcohol consumption over time*

Abstract: Meta-analysis (eight general population longitudinal studies) describes the relationships (regressions) between quantity per occasion and depressive symptomatology over time. Quantity and depression are the strongest and most consistent predictors of final levels of themselves in all data sets. Age significantly and consistently predicts quantity for both sexes combined (the general pattern is replicated among males only). Depression significantly predicts quantity and quantity significantly predicts depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
101
5
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(123 citation statements)
references
References 24 publications
10
101
5
7
Order By: Relevance
“…FHP women have a higher incidence of depression and lower incidence of alcoholism compared to FHP men suggesting that different pathophysiological mechanisms underlie alcoholism for men and women (Helzer and Pryzbeck 1988;Hartka et al 1991). One can speculate that the unique hormonal profile in FHP men compared to the other groups is somehow related to differences in the heritability of alcoholism for men and women.…”
Section: Discussionmentioning
confidence: 94%
“…FHP women have a higher incidence of depression and lower incidence of alcoholism compared to FHP men suggesting that different pathophysiological mechanisms underlie alcoholism for men and women (Helzer and Pryzbeck 1988;Hartka et al 1991). One can speculate that the unique hormonal profile in FHP men compared to the other groups is somehow related to differences in the heritability of alcoholism for men and women.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the findings seem to agree with the extant body of research on the issue. Thus, while a link between depression and heavier drinking has been found repeatedly [1][2][3][4], the association between anxiety and alcohol use seems less clear. It is true that both forms of emotional distress rarely have been assessed in one and the same study, but Skogen et al [49] recently reported that depressive symptoms were related to frequent intoxication among late teen youth, while symptoms of anxiety were not.…”
Section: Discussionmentioning
confidence: 99%
“…
IntroductionDepression has generally been found to be associated with heavy drinking and alcohol use disorders [1][2][3][4]. There is also evidence of a link between anxiety and extensive use of alcohol [5][6][7][8], but this association has been less extensively scrutinized and the findings seem less clear.
…”
mentioning
confidence: 99%
“…Some support for the role of MDEs as precursors of later alcohol disorders comes from follow-up studies of alcohol-related outcomes in individuals with earlier onset major depressions (e.g., Crum et al, 2008). On the other hand, at least one report noted a tendency for a decrease in alcohol use following depressive syndromes (Hartka et al, 1991), and several studies found no signifi cant increase in later AUDs for individuals with childhood and adolescent depressive episodes, while these same subjects demonstrated the expected increased risk for major depressions at follow-up (Ferguson and Woodward, 2002;Harrington et al, 1990;Rao et al, 1995;Weissman et al, 1999).…”
mentioning
confidence: 99%